Reaching a Tipping Point: A Qualitative Exploration of Quality of Life and Treatment Decision-Making in People Living With Benign Prostatic Hyperplasia. (November 2022) - Husted, Margaret; Gray, Debra; Golding, Sarah E.; Hindley, Richard
Benign prostatic hyperplasia (BPH) is a common condition amongst older men and is associated with lower urinary tract symptoms and erectile dysfunction; these symptoms can be burdensome and negatively affect quality of life. Various surgical and pharmaceutical treatment options exist but there is a paucity of qualitative research exploring men's decision-making when seeking BPH treatment. This study qualitatively explored men's experience of living with BPH and seeking treatment for BPH. Twenty men (aged 52–75) were recruited from outpatient urology clinics at a hospital trust in Southern England. Data were collected using semi-structured interviews (via video or telephone call) and were audio-recorded; transcripts were analysed using thematic analysis. Four themes were generated: 'Impacts are about more than just physical symptoms', 'The path towards treatment', 'The process of information gathering' and 'Navigating hopes, fears and uncertainty'. Results indicate most men appear to seek treatment for BPH following a gradual, and sometimes lengthy, period of deterioration in symptoms; for some men, however, treatment seeking follows an acute episode of sudden or severe symptoms. The decision to proceed with surgical or minimally invasive treatment options appears to be dependent on men reaching a tipping point; they no longer perceive their symptoms as tolerable and feel their ability to cope with symptoms is reduced. Men each bring their own set of concerns and preferences about side effects and risk-benefit profiles of different treatments. Clinicians need to be sensitive to these individual differences and incorporate them into shared decision-making for choosing between treatment options for BPH.